Arterial Network Geometric Characteristics and Regulation of Capillary Blood Flow in Hamster Skeletal Muscle Microcirculation - Lapi, Dominga; Di Maro, Martina; Mastantuono, Teresa; Starita, Noemy; Ursino, Mauro; Colantuoni, Antonio (Frontiers in Physiology, 2019)
This study was aimed to characterize the geometric arrangement of hamster skeletal muscle arteriolar networks and to assess the in vivo rhythmic diameter changes of arterioles to clarify regulatory mechanisms of the capillary perfusion. The experimental study was carried out in male Syrian hamsters implanted with a plastic chamber in the dorsum skin under pentobarbital anaesthesia. The skeletal muscle microvessels were visualized by fluorescence microscopy. The vessel diameters, lengths and the rhythmic diameter changes of arterioles were analyzed with computer-assisted techniques. The arterioles were classified according to a centripetal ordering scheme. In hamster skeletal muscle microvasculature the terminal branchings, differentiated in long and short loops, originated from anastomotic vessels, defined "arcading" arterioles. The long loops presented different frequencies along the branching vessels; order 4 arterioles had frequencies lower than those observed in the order 3, 2 and 1 vessels. The short loop order 3 arterioles, directly originating from "arcading" parent vessels, showed a frequency dominating all daughter arterioles. The amplitude of diameter variations in larger vessels was in the range 30-40% of mean diameter, while it was 80-100% in order 3, 2 and 1 vessels. Therefore, the complete constriction of arterioles, caused an intermittent capillary blood perfusion. L-arginine or papaverine infusion caused dilation of arterioles and transient disappearing of vasomotion waves and induced perfusion of all capillaries spreading from short and long loop arteriolar arrangements. Therefore, the capillary blood flow was modulated by changes in diameter of terminal arterioles penetrating within the skeletal muscle fibres, facilitating redistribution of blood flow according to the metabolic demands of tissues.